Do generalists profit from the fund families' specialists? Evidence from mutual fund families offering sector funds - Marc-André Göricke (University of Cologne, Centre for Financial Research (CFR), 2016)
This paper analyzes how the existence of sector funds (specialists) within a mutual fund family affects the performance and investment behavior of affiliated diversified equity funds (generalists). First of all, I show that specialists have stock picking skills. Second, information flows from the specialist to the generalist. The overlap in specialist and generalist industry sub-portfolios is positively related to the past track-record of the specialist in this industry and specialist work experience and negatively related to the overall work experience and the industry track-record of the generalist. Generally, stocks held by specialists appear in more diversified funds of the family than other stocks. As a result, diversified funds from fund families with sector funds perform better, trade more, and hold more hard-to-value stocks than their peers from families without sector funds.
Keywords: D23; D83; G23; G24; 330; mutual funds; fund families; analyst skills; manager skills; information sharing; fund performance; investment behavior